Health risk assessment of children’s and adult’s exposure to arsenic bound to PM10 in the city of Bor - Petrović, Bojana; Gladović, Ana; Javorac, Dragana; Buha Djordjević, Aleksandra; Ćurčić, Marijana; Djukić-Ćosić, Danijela; Šoštarić, Andrej; Antonijević, Biljana; Bulat, Zorica (Archives of Pharmacy, 2022)
One of the most polluted cities in Serbia and Europe is Bor, due to mining and smelting processes in Mining-Metallurgical Complex in Bor. Mining activities release mainly SO2 and paritculate matter in air and, as arsenic is usually found in copper and lead ores, air quality monitoring in Bor has been showing its presence in exceeded annual limit concentrations in past few years. Exposure to arsenic is related with anemia, skin changes, peripheral neuropathy and cancer development. This study was carried out to assess children’s and adult’s exposure to arsenic bound to PM10 and to charcterize risk from their exposure through the air in the city of Bor. Mean yearly concentrations of arsenic were used from Reports of the Serbian Enviromental Protection Agency, for measuring stations: Bor-City park, Bor 1, Bor 2 and Bor-Jugopetrol. The USEPA method was used to assess non-carcinogenic and carcinogenic risk, which classifies non-carcinogenic risk as acceptable (1) based on hazard quotient (HQ) values for three main exposure pathways, while cancer risk classification is based on CR values also as acceptable (1×10-4). HQinh values exceeded safe level both for children and adults on all measuring stations, describing risk as unacceptable via inhalation exposure. Unacceptable carcinogenic risk for children was calculated on measuring station Bor-Jugopetrol and for adults on measuring stations Bor-City park, Bor 1 and Bor-Jugopetrol. Actions for reduction of arsenic release into the air should be taken due to obtained results for city of Bor.